Justice Beyond Legal Religious Formalism: Moral Perspectives in Law Enforcement Practices - Yani, Akhmad; Mispansyah; Ahmad Syaufi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The relationship between law, justice, and morality remains central in legal philosophy, yet much of the discourse remains normative and detached from real-world enforcement . Purpose: This study aims to empirically examine how moral frameworks influence the practice of law enforcement, particularly within contexts shaped by Islamic jurisprudence and local socio-cultural norms.. Methods: The research draws on semi-structured interviews with law enforcement officers, analysis of court cases, and ethnographic observation in Indonesian legal settings . Findings: Findings reveal that moral considerations rooted in religious values and communal ethics significantly shape interpretations and enforcement decisions, often mediating tensions between codified state law and local moral expectations. The evidence also shows that while positivist approaches dominate formal structures, natural law reasoning and socio-cultural ethics remain influential in practice. Theoretical and Practical Implications: The study bridges philosophy of law with empirical socio-legal research, offering insights into how morality operates as a determinant in justice delivery and conflict resolution. Originality/Novelty: This research contributes by integrating anthropological fiqh with legal philosophy, providing a culturally grounded and empirically validated framework for understanding morality in law enforcement